Proof of Marital Status Not Recorded on Family Card - Taufiqullatif, Muhammad (Damhil Law Journal, 2021)
The Family Card is an authentic deed whose evidentiary power is binding and perfect. The family card should be perfectly crafted, and there are no errors or doubts of the data in it. If there are changes in data should be immediately reported and corrected to the authorized agencies. Making family cards and birth certificates without attaching a marriage certificate citation according to the latest regulations has degraded the correctness of the data in the family card. In proving the status of marriage in the family card basically must still attach a marriage certificate citation because the marriage certificate quote is the only evidence that proves the validity of marriage for Muslims in Indonesia. Â Even if the manufacture of Family Card is allowed with a Statement Of Absolute Responsibility and 2 (two) witnesses, it should still be examined conditions harmoniously. There is no violation of the prohibition of marriage to prove the validity of the wedding because based on the fact of the marriage will bring up the name of the father in the column of parents of the child. The purpose of this study is so that policymakers and product users do not misinterpret or interpret the description "undocumented marriage" on the family card. The research methodology of this journal is a descriptive normative approach that is qualitatively analyzed based on research on legislation and books and periodicals on marriage and marriage recording.